Optimizing Mediation Assistance as a Realization of Fair Dispute Resolution through the "Ayo Mediasi" Application - Yana Indawati; Shinfani Kartika Wardhani; Sascha Zahra Vernanda (Journal of Law, Politic and Humanities, 2024)
Mediation, as defined in Article 1 point 1 of the Supreme Court Regulation (PERMA) No. 1 of 2016 concerning Mediation Procedures in Court, is a method of settlement that uses a negotiation process to reach an agreement between the parties with the assistance of a Mediator. Mediation must be used as a tool to reduce the number of civil cases in court. This study intends to achieve the ease of implementing mediation with high transmission, confidentiality of the parties' names, shorter phases, a quick process, and easy access to the community. This is a descriptive analytical study that takes a normative legal approach. The results of this research show that mediation service providers use the "Ayo Mediasi" application to resolve civil matters outside of prosecution, collaborate with mediators from professional law firms, and are eager to invite the parties to reconcile.